2014
DOI: 10.1523/jneurosci.1971-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Blood Flow in the Retinal Trilaminar Vascular Network

Abstract: Light stimulation evokes neuronal activity in the retina, resulting in the dilation of retinal blood vessels and increased blood flow. This response, named functional hyperemia, brings oxygen and nutrients to active neurons. However, it remains unclear which vessels mediate functional hyperemia. We have characterized blood flow regulation in the rat retina in vivo by measuring changes in retinal vessel diameter and red blood cell (RBC) flux evoked by a flickering light stimulus. We found that, in first-and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
176
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(195 citation statements)
references
References 59 publications
16
176
3
Order By: Relevance
“…Specifically, Kornfield et al 22 observed 11% increase in the superficial RBF following 2-second flicker stimulation by using functional MRI (BOLD), which compares well with the~10% increase we measured with DOCT for flicker stimulus of the same duration. Radhakrishnan et al 23 reported~12% blood flow increase for a 10-second flicker stimulus using en-face Doppler OCT, while Werkmeister et al 24 detected over 30% increase of blood flow with 60-second flicker stimulus using DOCT.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, Kornfield et al 22 observed 11% increase in the superficial RBF following 2-second flicker stimulation by using functional MRI (BOLD), which compares well with the~10% increase we measured with DOCT for flicker stimulus of the same duration. Radhakrishnan et al 23 reported~12% blood flow increase for a 10-second flicker stimulus using en-face Doppler OCT, while Werkmeister et al 24 detected over 30% increase of blood flow with 60-second flicker stimulus using DOCT.…”
Section: Discussionsupporting
confidence: 87%
“…Offline, a software package (NIS Elements version 4.0) facilitated the lumen measurements used to calculate the change in mean diameter during exposure to experimental solutions. Of note, similar to in vivo observations (32), changes in lumen diameter of arterioles in ex vivo retinas were not uniform along a vessel; this study used the maximal change detected within the well-focused portion (∼25-μm long) of a monitored vessel.…”
Section: Methodsmentioning
confidence: 70%
“…Rat experiments indicate that flicker stimulation evokes larger dilations in the intermediate layer capillaries than in the superficial and deep layer capillaries. 55 Recently, Duan et al 56 reported a vasodilation of 13% 6 5% in the precapillary arterioles, 31% 6 8% in the capillaries, and 10% 6 3% in the postcapillary venules by using adaptive optics imaging in the human retina while applying focal patches of flickering visible light. For the above reasons, although showing a clear trend, the increases in the power fit exponents as calculated by the model are lower than the ones observed in vivo.…”
Section: Discussionmentioning
confidence: 99%